2015
DOI: 10.1002/prep.201400249
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Composite Nano‐RDX by RESS Co‐Precipitation

Abstract: N anoscalec omposites of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and polymeric bindersw ere produced by co-precipitation using rapid expansion of supercritical solutions( RESS). The binders used in this study are poly (vinylidene fluoride-co-hexafluoropropylene) (VDF-HFP 22 )a nd polystyrene (PS). The RDX/VDF-HFP 22 and RDX/PS co-precipitatedn anoparticles were characterized by Scanning Electron Microscopy( SEM) and Transmission Electron Microscopy( TEM). The average size of produced nanoparticles is ca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…[249] Supercritical CO 2 was pumped at ac onstant mass flow rate throught he extraction vessela t1 3.0-20.5 MPa and 48-53 8C. [249] Supercritical CO 2 was pumped at ac onstant mass flow rate throught he extraction vessela t1 3.0-20.5 MPa and 48-53 8C.…”
Section: Hem Processing With Supercritical Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[249] Supercritical CO 2 was pumped at ac onstant mass flow rate throught he extraction vessela t1 3.0-20.5 MPa and 48-53 8C. [249] Supercritical CO 2 was pumped at ac onstant mass flow rate throught he extraction vessela t1 3.0-20.5 MPa and 48-53 8C.…”
Section: Hem Processing With Supercritical Fluidsmentioning
confidence: 99%
“…Nanoparticles of RDX were coated with polystyrene or poly-(vinylidenef luoride-co-hexafluoropropylene) (VDF-HFP 22 )p olymer films by RESS-type coprecipitation. [249] Supercritical CO 2 was pumped at ac onstant mass flow rate throught he extraction vessela t1 3.0-20.5 MPa and 48-53 8C. The poorly soluble RDX precipitated first, and then the polymer deposited on the surfaceo ft he RDX nanoparticles.…”
Section: Hem Processing With Supercritical Fluidsmentioning
confidence: 99%
“…As one class of them, nano-explosives have attracted much attention due to their potential application in micro thrusters [6] and micro-electromechanical systems [7]. Recently, benefiting from the development of nanotechnology, a variety of nano-explosives such as 1,3,5-trinitro-1,3,5-triazinane (RDX) [8,9], HMX [10,11], 1,1-diamino-2,2-dinitroethene (FOX-7) [12,13], 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazawurt-zitane (CL-20) [14,15] and TATB [16,17] have been successfully prepared by various approaches. With respect to LLM-105, Zhang et al [18] utilized a spray-crystalline method to prepare submicron size LLM-105.…”
mentioning
confidence: 99%
“…8 Similar studies were also reported by Wang et al 9 and Bayat et al 10 ; they prepared nano-CL-20 via ultrasonic sprayassisted electrostatic adsorption technology and micro emulsion method, respectively. Furthermore, to reduce the sensitivities of explosives, other nanoenergetics also were reported, such as nano-HMX, [11][12][13][14][15] nano-RDX, [16][17][18] nano-NTO, 19 nano-HNS, 20,21 and nano-TATB. 22,23 The energetic nanocomposites are another form of nanoenergetics.…”
Section: Introductionmentioning
confidence: 99%